Respuesta :

Answer: x=-3    y=7.

Step-by-step explanation:

[tex]\displaystyle\\\left \{ {{6x+4y=10\ \ \ \ \ (1)} \atop {12x+y=-29\ \ \ \ (2)}} \right.\\ We\ multiply\ both\ sides\ of\ equation\ (1)\ by\ -2:\\\left \{ {{(-2)*6x+(-2)*4y=(-2)*10} \atop {12x+y=-29}} \right. \\\\\left \{ {{-12x-8y=-20} \atop {12x+y=-29}} \right. \\[/tex][tex]We\ summarize\ equations\ (1)\ and\ (2):\\-7y=-49\\-7*y=-7*7\\Divide\ both\ sides\ of\ the\ equation\ by\ -7:\\y=7.\\We\ substitute\ the\ value\ of\ y\ into \ equation\ (1):\\6x+4*7=10\\6x+28=10\\6x+28-28=10-28\\6x=-18\\6*x=6*(-3)\\Divide\ both\ sides\ of\ the\ equation\ by\ 6:\\x=-3.[/tex]